Exploring the Effectiveness, Features, and Compatibility of MongoDB and MySQL: A Comprehensive Comparison of NoSQL and Relational Databases - SOWANDI, CHELSEA MARCHELLE; LEONITA, IVANA; ARISAPUTRA, STEVEN HARTANTO PANJI; DAVID, DAVID (MIND (Multimedia Artificial Intelligent Networking Database) Journal, 2023)
AbstrakDi era digital ini, data menjadi aset yang sangat berharga bagi bisnis dan organisasi.Â  Terdapat jenis database yang umum digunakan, yaitu Database Relasional dan Database NoSQL. Perbandingkan antara kedua jenis database tersebut dibahas melalui analisis perbedaan dan dampak praktisnya. Evaluasi terhadap kedua jenis database ini dilakukan untuk menentukan platform database terbaik yang sesuai dengan kebutuhan organisasi. Penelitian ini membahas perbandingan MongoDB dengan MySQL. Analisis, kelebihan, dan keterbatasan dari masing-masing jenis database ini, serta hal yang mempengaruhi pemilihan platform database dibahas pada penelitian ini. Dengan membandingkan fitur dan kasus penggunaan kedua database ini, diharapkan dapat memberikan wawasan berharga yang dapat membantu organisasi membuat keputusan yang tepat saat memilih platformÂ database.Kata kunci: database, Database NoSQL, MongoDB, MySQL, platform databaseAbstractIn today's digital age, data has become an essential asset for businesses and organizations. Databases are used to store, manage, and update information, providing reliable and organized data that can be accessed and analyzed as needed. There are several types of databases, including Relational Databases and NoSQL Databases. This paper compares the two types of databases, analyzing their differences and practical implications. We examine the aspects of both type of database to determine the best database platform for specific organizational needs. Specifically, we compare MongoDB, a popular NoSQL Database, with MySQL, a widely used Relational Database. Our analysis considers the strengths and limitations of each type of database, and how they impact the selection of a database platform. By comparing the features and use cases of these databases, we provide valuable insights that can help organizations make informed decisions when selecting a database platform.Keywords: databases, NoSQL Databases, MongoDB, MySQL, database platform